Time dependence of hydraulic parameters estimation from transient analysis of mini disc infiltrometer measurements. (15th March 2022) - Naik, Aparimita Priyadarshini; Pekkat, Sreeja
Abstract: The transient analysis of mini disc infiltrometer (MDI) measurements is an established method for characterising near‐surface hydraulic characteristics of soils. The reliability of hydraulic characteristics obtained from transient analysis depends on the (1) adequacy of model, (2) adequacy of data, (3) measurement time and (4) measurement footprint. The measurement time dependence recommendations are reported only for a few soil textures, initially wet samples and tension infiltrometer (TI) with a higher measurement footprint than the MDI. This study investigated the adequacy of infiltration data (using cumulative linearization [CL] and differentiated linearization [DL]) and measurement time influence on the hydraulic parameters determined from the transient analysis of MDI measurements for six soil textures. The objective of the study is to identify suitable MDI measurement durations for different soil textures for the initially dry state, considering both adequacy of data and time fractionation (measurement time influence). The data adequacy time obtained from the DL ( T DL ) was found to be 0.8 times less than the value obtained from CL ( T CL ). The marginal difference in T DL and T CL had a significant influence on the determination of infiltration equation coefficient C 1 and negligible influence on coefficient C 2 . The time fractionation procedure adopted for identifying adequate MDI measurement time ( T m ) was found to be comparable based on sorptivity ( S 0 ) and hydraulic conductivity ( K 0 ). The average T m was also comparable with T DL and T CL with a strong positive correlation. The C 2 values obtained based on T m, T DL, and T CL were in better agreement than the corresponding C 1 values. The adequate MDI measurement times identified by considering T m, T DL, and T CL were texture dependent, ranging from 45 min for silt to 120 min for silt loam and silty clay loam. For loamy sand, it was 50 min; for sand, it was 70 min, followed by 60 min for loam. Highlights: Detailed assessment of influence of MDI measurement time ( T m ) on infiltration coefficients C 1 and C 2 and hydraulic parameters K 0 and S 0 . MDI measurement time duration to be considered based on the adequacy of data check by CL and DL methods (designated as T CL and T DL ). Recommendation on the measurement duration, T m for MDI for six different soil textures. Variability of C 1, C 2, K 0 and S 0 for the time duration T m, T CL and T DL .